Faktor-Faktor yang Mempengaruhi Kepatuhan Pengobatan Pasien TB Paru - Mariyana Nauw; Fery Agusman Motuho Mendrofa (Jurnal Sehat Mandiri, 2025)
Treatment adherence in tuberculosis (TB) patients is influenced by social, psychological, and health system factors. This study aims to identify factors that influence treatment adherence in pulmonary TB patients. This study adopted the MIX Methods with a sequential explanatory approach, consisting of quantitative and qualitative phases conducted from June to August 2025. The quantitative phase used a cross-sectional approach to identify factors that influence the availability of treatment for pulmonary TB patients at the Teluk Bintuni Community Health Center. The qualitative phase was conducted through in-depth interviews to understand the influence of variables on treatment adherence. The study population was 60 TB patients who met the inclusion criteria, with an emphasis on research ethics according to established guidelines. Data analysis included univariate, bivariate, and multivariate analyses as well as triangulation to validate the results. The results showed that knowledge, motivation, access to health facilities, family support, and support from health workers played a significant role in improving well-being. Patient motivation was the dominant factor with an Odds Ratio (OR) of 6.764, followed by family support (OR 6.277) and healthcare provider support (OR 5.575). In conclusion, patients with good knowledge were 7.63 times more likely to adhere to treatment, while easy access to healthcare facilities increased the likelihood of adherence by 6.29 times. Emotional and instrumental support from family and effective communication with healthcare providers proved important.